Comparison of direct renin inhibitor and angiotensin II receptor blocker on clinic and ambulatory blood pressure profiles in hypertension with chronic kidney disease. (16th November 2016) - Uneda, Kazushi; Tamura, Kouichi; Wakui, Hiromichi; Azushima, Kengo; Haku, Sona; Kobayashi, Ryu; Ohki, Kohji; Haruhara, Kotaro; Kinguchi, Sho; Ohsawa, Masato; Fujikawa, Tetsuya; Umemura, Satoshi
ABSTRACT: We compared the therapeutic effects of aliskiren (direct renin inhibitor (DRI) group) with angiotensin II (Ang II) type 1 receptor blockers (ARBs) (ARB group) on clinic blood pressure (BP) and ambulatory BP in 36 hypertensive chronic kidney disease (CKD) patients. The baseline clinic BP levels and the after-treatment/baseline ( A / B ) ratios of clinic BP levels, estimated after 24-week treatment period, were similar in DRI group ( n = 18) and ARB group ( n = 18). With respect to the effects on ambulatory BP, the A / B ratios of the daytime and nighttime systolic BP in DRI group were significantly higher than those in ARB group. The A / B ratio of ankle-brachial pressure index after the study was higher in the DRI group compared with the ARB group. The results of the present study suggest that DRI therapy is not superior to ARB therapy in lowering ambulatory BP in hypertensive CKD patients, in spite of comparable clinic BP-lowering effects.